2002
DOI: 10.1021/ma020118v
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Nitroxide-Terminated Poly(n-butyl acrylate) Prepared in Bulk and Miniemulsion Polymerizations

Abstract: The structure of “living” poly(n-butyl acrylate) homopolymers prepared via nitroxide-mediated controlled radical polymerization in bulk and in miniemulsion at 112 °C was examined by SEC, NMR, and MALDI−TOF mass spectrometry in order to study the influence of chain transfer to polymer. The absence of detectable terminal unsaturation was confirmed by proton NMR. The branched structure was observed by 13C NMR. MALDI−TOF MS demonstrated that the majority of chains, even at high conversion, had the ideal structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
173
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(184 citation statements)
references
References 26 publications
10
173
1
Order By: Relevance
“…In one of the earliest studies employing mass spectrometry to elucidate chain-end structures in acrylate polymerizations, Charleux and coworkers imaged polyBA prepared via NMP. 37 These authors concluded that at elevated temperatures (T [ 112 C) intramolecular chain transfer via backbiting (as defined earlier in Scheme 4) is observed, although the majority of all chains had a structure with the initiator fragment at one end and the nitroxide at the other. Contemporarily, Grady et al 69 employed FT-ESI-MS to study the high-temperature polymerization (T ¼ 120 C) of the butyl acrylate in xylene solution and identified a range of b-scission and macromonomer products that support the notion that such side reactions are responsible for reducing the observable molecular weight as well as limiting the rate of polymerization.…”
Section: Mass Spectrometry Of Acrylate Polymersmentioning
confidence: 94%
See 1 more Smart Citation
“…In one of the earliest studies employing mass spectrometry to elucidate chain-end structures in acrylate polymerizations, Charleux and coworkers imaged polyBA prepared via NMP. 37 These authors concluded that at elevated temperatures (T [ 112 C) intramolecular chain transfer via backbiting (as defined earlier in Scheme 4) is observed, although the majority of all chains had a structure with the initiator fragment at one end and the nitroxide at the other. Contemporarily, Grady et al 69 employed FT-ESI-MS to study the high-temperature polymerization (T ¼ 120 C) of the butyl acrylate in xylene solution and identified a range of b-scission and macromonomer products that support the notion that such side reactions are responsible for reducing the observable molecular weight as well as limiting the rate of polymerization.…”
Section: Mass Spectrometry Of Acrylate Polymersmentioning
confidence: 94%
“…As a consequence, those chains are not only branched but also continue to grow at twice the rate compared with their linear counterparts. In fact, such behavior was tested for by Charleux and coworkers in NMP of BA via MALDI-ToF mass spectrometry 37 (see ''Mass Spectrometry of Acrylate Polymers'' section for details) and later observed by Boschmann and Vana via comparison of UV and refractive index signal in SEC analysis of RAFT-made star polymers. 38 In their study, they used the UV signal to detect the concentration of RAFT groups per chain which was then compared with the polymer concentration as determined from the RI detector.…”
Section: Mcr Formation Via Intermolecular Transfer To Polymermentioning
confidence: 99%
“…For simplicity, intermolecular chain transfer to polymer is neglected since literature reports indicate that LCBs barely contribute to the total branching content. [15,[19][20][21][22][23] Similarly, termination by disproportionation [65,66] and addition reactions involving macromonomers are neglected in a first approximation. [67] The ATRP catalyst and initiator are the same as those used by Ahmad et al [32] in their experimental study of the bulk normal ATRP of nBuA at 378 K, i.e., CuBr/PMDETA and methyl 2-bromopropionate (MBrP).…”
Section: Kinetic Modelmentioning
confidence: 99%
“…However, several kinetic studies have indicated that the contribution of LCBs to the total amount of branches is very low, especially at low to intermediate conversions. [15,[19][20][21][22][23] In contrast to RP of ethylene and vinyl acetate in which the occurrence of chain transfer to polymer reactions is a long-standing fact that has been well documented since its discovery more than a half century ago, [24][25][26][27][28] the importance of branching in acrylate RP has only emerged in the early nineties by the detection of quaternary carbons via 13 C NMR spectroscopy. [29][30][31] Interestingly, Ahmad et al [32] have recently reported that the branching level of poly(nbutyl acrylate) can be reduced significantly by performing a CRP instead of an FRP.…”
Section: Introductionmentioning
confidence: 99%
“…The other problem is the relative high rate of alkoxyamine disproportionation, an undesirable reaction that causes negative impact on the living character of these systems at high temperature. 176 A promising approach is the use of nitroxides that exhibit reversible cleavage at lower temperature allowing reduced polymerization temperature of 90-100 C. These nitroxides are illustrated in Figure 3 and include SG1, 171,172 SG1-based water-soluble alkoxyamine(SG1-A-Na), 173 and TEMPO-terminated oligomers of PS (TTOPS). 176 Compartmentalization of growing radicals in conventional free radical polymerization increases the rate of polymerization (R p ) and the molecular weight of polymer.…”
Section: Crp In Miniemulsionmentioning
confidence: 99%